OPTIMASI STRUKTUR UNTUK MENDAPATKAN FREKUENSI ALAMI YANG TERPISAHKAN SECARA OPTIMAL - Satryo Soemantri B; I Wayan Suweca; Endra Sujatmika (Mesin, 1998)
In obtaining the dynamic response of a dynamic system, its uncouple modal equation of movement simplifies the usage of superposition modal method. This paper proposes a strategy to obtain the uncouple modal equation based an hypotheses of Basile :